When I Feel Afraid = Jab Mujhay Dar Lagta Hai - Meiners, Cheri J.; Illustrated by Johnson, Meredith (Karachi Oxford University Press, 2016)
Explains that many things can be frightening and provides examples of what one can do to feel less afraid, such as asking for help from a person one trusts. Includes information and extension activities for parents or teachers.
Children today have many fears, both real and imagined. Encouraging words and supportive illustrations guide children to face their fears and know where to turn for help. Little ones also learn simple ways to help themselves. Includes a special section for adults, with ideas for supporting children when they feel afraid and a list of additional resources.
Include Illustrations.
Keywords: Fear in children -- Juvenile literature -- Fear -- Conduct of life